TaRPM1 Positively Regulates Wheat High-Temperature Seedling-Plant Resistance to Puccinia striiformis f. sp. tritici - Wang, Jiahui; Tian, Wei; Tao, Fei; Wang, Jingjing; Shang, Hongsheng; Chen, Xianming; Xu, Xiangming; Hu, Xiaoping (Frontiers in Plant Science, 2020)
RPM1 is a CC-NBS-LRR protein that was first shown to be required for resistance to Pseudomonas syringae pv. maculicola in Arabidopsis thaliana. Our previous study showed that TaRPM1 gene in wheat was up-regulated about six times following infection by Puccinia striiformis f. sp. tritici (Pst) under high temperature, compared with normal temperature. To study the function of TaRPM1 in wheat high-temperature seedling-plant (HTSP) resistance to Pst, the full length of TaRPM1 was cloned, with three copies each located on chromosomes 1A, 1B and 1D. Transient expression of the TaRPM1-GFP fusion protein in Nicotiana benthamiana indicated that TaRPM1 localizes in the cytoplasm and nucleus. Profiling TaRPM1 expression indicated that TaRPM1 transcription was rapidly up-regulated upon Pst inoculation under high temperature. In addition, TaRPM1 was induced by exogenous salicylic acid hormone application. Silencing TaRPM1 in wheat cultivar Xiaoyan 6 (XY 6) resulted in reduced HTSP resistance to Pst in terms of reduced number of necrotic cells and increased uredinial length, whereas no obvious phenotypic changes were observed in TaRPM1-silenced leaves under normal temperature. Related defense genes TaPR1 and TaPR2 were down-regulated in TaRPM1-silenced plants under high temperature. We conclude that TaRPM1 is involved in HTSP resistance to Pst in XY 6.